The complete guide to strength training / Anita Bean. - Bean, Anita (A. & C. Black, 2005)
This is a guide for anyone looking to increase their strength and resculpt their body. It provides a combination of effective training methods and cutting-edge nutritional guidance and delivers a comprehensive training programme adaptable for beginner and advanced trainer alike.